Administrative Delay, Red Tape, and Organizational Performance. Issue 3 (4th May 2019) - Kaufmann, Wesley; Taggart, Gabel; Bozeman, Barry
Abstract: We focus on the relationships among administrative delay, red tape, and red tape–related organizational performance. We hypothesize that administrative delay leads to more red tape, more complaints from clients about red tape, and makes it more difficult for organizations to serve their clients. We test our hypotheses using data from the National Administrative Studies Project - Citizen, gathered on Amazon Mechanical Turk in late 2014 ( n  = 1, 254). The results support each of the hypotheses. The findings imply that managers may improve organizational performance by identifying and addressing the specific sources of administrative delay, rather than focusing on general perceptions of organizational red tape.